Feeding Preferences and Reproduction of the False Powder Post Beetle, Sinoxylon anale Lesne, on Two Clones of the Pará Rubber Tree - Sittichaya, Wisut; Ngampongsai, Aran; Permkam, Surakrai; Puangsin, Buapan (Agriculture and Natural Resources, 2012)
The feeding preference and reproduction of Sinoxylon anale on two rubberwood clones (PB235, RRIM600 and the main branch of clone RRIM600) were investigated. No-choice and multiple-choice feeding tests were designed to determine the feeding preference of the beetle, whereas laboratory reared beetles were used for reproductivity measurements. Adult S. anale preferred rubberwood clone PB235 over both types of wood from clone RRIM600. In a multiple choice test, 60% of the beetles chose rubberwood clone PB235, and of the remainder, 24% and 16% chose wood from the trunk and branch of clone RRIM 600, respectively. The adult beetles also showed a highly significant (P < 0.001) preference for feeding on wood from clone PB235 (0.295 ± 0.028 g) over trunk wood from clone RRIM 600 (0.253 ± 0.029 g) but there was no significant difference in the preference shown for wood from the RRIM600 branch (0.275 ± 0.021g). S. anale also produced the greatest number of progeny in clone PB235 (39.07 ± 17.30 individuals), significantly greater (P < 0.01) than the number produced in the trunk wood (25.73 ± 8.41 individuals) and the branch wood (22.47 ± 2.73 individuals) from the RRIM600 clones. The results indicated that S. anale seemed to prefer (as well as being more reproductive in) wood with a higher starch content.